Analysis of Taxpayer Compliance Level in Paying Land and Building Tax Case Study: City of Surabaya - Arifah, Dania Nur; Marseto, Marseto; Wijaya, Riko Setya (Unram Journal of Community Service, 2025)
This study examines the compliance level of taxpayers in paying Land and Building Tax (PBB) in Surabaya City, a significant source of local revenue. The research aims to identify factors influencing taxpayer compliance and assess the effectiveness of existing tax administration services. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal varied compliance levels across different UPTB areas, with key influencing factors including tax awareness, service quality, and enforcement of penalties. This study contributes to understanding taxpayer behavior in urban settings and offers insights for policymakers to enhance tax compliance through improved service quality and targeted educational campaigns.